Strategi Sukses Melalui Usaha Mikro Dan Kecil Untuk Meningkatkan Pendapatan Keluarga - Astuti Kelian; Ambarwati Fatonah; Wili .; Veta Lidya Delimah Pasaribu (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Community service with the theme "Successful Strategies for Starting Micro and Small Businesses to Increase family Income at SMA Pelita Bangsa" aims to provide students with practical knowledge and skills in starting and managing micro and small businesses effectively. Given that micro and small businesses play a strategic role in improving family economic welfare, this activity is designed to encourage students to become entrepreneurs from an early agewith the right strategies. The methods used in implementing the activity included entrepreneurship training, group discussions, business simulations, and direct mentoring that emphasized a practical approach. The results of this activity showed an increase in students' understanding of important aspects of starting a business, including business planning, simple financial management, product development, and marketing increative and efficient ways. In addition, this activity builds students' confidence to try business ideas that can provide additional income for their families. It is hoped that this activity will not only stop after implementation, but can also be a stepping stone for the creation of a generation of independent and resilient young entrepreneurs at Pelita Bangsa High School. The results of this activity showed an increase in students' understanding of important aspects of starting a business, including business planning, simple financial management, product development, and marketing increative and efficient ways. In addition, this activity builds students' confidence to try business ideas that can provide additional income for their families. It is hoped that this activity will not only stop after implementation, but can also be a stepping stone for the creation of a generation of independent and resilient young entrepreneurs at Pelita Bangsa High School.